IDENTIFYING PRE-HOSPITAL FACTORS WHICH INFLUENCE OUTCOME FOR MAJOR TRAUMA PATIENTS IN A REGIONAL TRAUMA NETWORK: AN EXPLORATORY STUDY. Issue 9 (18th August 2016) - Thompson, Lee; Hill, Michael; Davies, Caroline; Shaw, Gary
Abstract : Background: Major trauma is often life threatening or life changing and is the leading cause of death in the United Kingdom for adults aged≤45 years. The aim of this exploratory study was to identify pre-hospital factors influencing patient outcomes for major trauma within the Northern Trauma Network. Method: Secondary data analysis of a combined data set of pre-hospital audit data and patient outcome data from the Trauma Audit Research Network (n=1033) was undertaken. Variables included mechanism of injury, age, physiological indices, timings and skill mix. Principle outcome measures included Mortality data and Glasgow Outcome Scales. Results: Glasgow Coma Scores proved a significant predictor of mortality in major trauma (p<0.00). Amongst other physiological indices, systolic blood pressure ≤90 mm Hg. was associated with both increased mortality (p≤0.004) and poorer morbidity (p≤0.021). Respiration rate <14/minute was also significantly predictive of morbidity (p≤0.03) and mortality (p<0.00). Prolonged response times to the most critically injured patients (p<0.031), and increasing casualty age were significantly associated with poorer outcomes. The attendance of a Doctor was significantly associated with increased mortality (p≤0.036) perhaps validating existing resource despatching practices. Predictors of positive outcomes included the presence of a Doctor when on-scene time ≤50 minutes (p≤0.015), crew arrival on-scene ≤10 minutes (p<0.046) and on-scene time ≤50 minutes (p<0.015). Conclusion: These findings validate GCS, BP and Respiratory Rate values as valid triggers for transport to a Major Trauma Centre. Analysis of the interactions between arrival time, time-on-scene, skill mix and age demand further exploration but tentatively validate the concept of a 'Golden Hour' and suggest the potential value of a 'load and go and play on the way' approach.